Language, data, and knowledge : first International Conference, LDK 2017, Galway, Ireland, June 19-20, 2017, Proceedings /: first International Conference, LDK 2017, Galway, Ireland, June 19-20, 2017, Proceedings. (2017) - Unknown
No abstract available